The effect of a project-based learning model based on 3d media on collaborative skills - Sholihah, Nailatus; Khoiri, Nur; Cahya Adi, Widi (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
Learning in the 21st century creates real changes in the world of education that focus on the learning process. One of the skills that students must have in the 21st century is collaborative skills. The learning model that can develop collaborative skills is the 3D media-based Project Based Learning model. The purpose of this research is to analyze the effect of Project Based Learning model based on 3D media on collaborative skills in biology learning. The novelty of this research is the use of a Project-Based Learning model based on 3D media. The type of research used in this research is quasi-experiment with Nonequivalent Control Group Design. The sampling technique used was Random Sampling, with class XI.1 as the experimental class and class XI.3 as the control class. The data collection techniques used in this study were interviews, observations, documentation, and pretest-posttest sheets of collaborative skills questionnaire. The results showed that there was an effect of 3D media-based Project Based Learning model on collaborative skills in biology learning, this can be seen from the One-Way Anacova test analysis of collaborative skills with a significance value of 0.000 <0.05.